2013
DOI: 10.1080/15459624.2012.760063
|View full text |Cite
|
Sign up to set email alerts
|

Manikin-Based Performance Evaluation of Elastomeric Respirators Against Combustion Particles

Abstract: This study investigated the effects of faceseal leakage, breathing flow, and combustion material on the overall (non-size-selective) penetration of combustion particles into P-100 half and full facepiece elastomeric respirators used by firefighters. Respirators were tested on a breathing manikin exposed to aerosols produced by combustion of three materials (wood, paper, and plastic) in a room-size exposure chamber. Testing was performed using a single constant flow (inspiratory flow rate = 30 L/min) and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
5
13
0
Order By: Relevance
“…The average size-selective TIL values obtained from this study were comparable to those reported in our previous study with a partially sealed (nose or nose–chin area) half-mask donned on a hard plastic manikin headform (He et al, 2013a,b), and 5- to 10-fold lower than those obtained with the unsealed half-mask donned on the plastic headform. This improvement can be attributed to the softness of the manikin skin, which deforms under stress, thus increasing the contact surface area and consequently forming a better seal.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The average size-selective TIL values obtained from this study were comparable to those reported in our previous study with a partially sealed (nose or nose–chin area) half-mask donned on a hard plastic manikin headform (He et al, 2013a,b), and 5- to 10-fold lower than those obtained with the unsealed half-mask donned on the plastic headform. This improvement can be attributed to the softness of the manikin skin, which deforms under stress, thus increasing the contact surface area and consequently forming a better seal.…”
Section: Resultssupporting
confidence: 87%
“…An elastomeric 3M 6000 series half-mask respirator equipped with two 3M 2091 P100 filters (3M Corp., St Paul, MN, USA) was chosen for the testing to assure the continuity of our previous research (He et al , 2013a,b). The rationale for selecting the above respirator was described in detail by He et al (2013a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 95% of the particles were in the size range of 20 to 150 nm. This is also consistent with previous studies (Baxter et al, 2010;He et al, 2013). To ensure sufficient particle number concentrations (especially downstream of the tested filters), the particle size-specific collection efficiency values were determined within a narrower range, 20-150 nm, in 8 channels.…”
Section: Particle Size Distributions Of Combustion Aerosolssupporting
confidence: 86%
“…This recommendation is aimed at improving the faceseal for the user, as faceseal leakage is the primary source of contaminant infiltration into a facepiece. (8) To accommodate this recommendation, NIOSH developed digital head form models to correspond to the face size categories of the PCA panel. These new head forms are intended to be more representative of the modern work force as they were developed using three-dimensional data collected from a subset of the anthropometric survey used to develop the panel.…”
mentioning
confidence: 99%